2009
DOI: 10.1007/s10869-009-9137-x
|View full text |Cite
|
Sign up to set email alerts
|

Attributions and Outcomes of Customer Misbehavior

Abstract: The purpose of this study is to determine which attribution dimensions concerning dysfunctional other-customer misbehavior most influence customer dissatisfaction toward a service firm. Our research hypotheses were tested using a 2 (Controllability: controllable versus uncontrollable) x 2 (Stability: unstable versus stable) x 2 (Globality: specific versus global) experimental design in a hypothetical restaurant context. Our empirical results demonstrate that when customers feel that the other-customer's misbeh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 35 publications
1
37
0
Order By: Relevance
“…The results of the empirical analysis reveal that vicarious embarrassment—in which person A feels embarrassed for person B—can occur in situations in which a customer interacts with another customer, as well as in situations in which a customer interacts with a service employee. Overall, by identifying various vicariously embarrassing incidents, the authors were able to support the results of prior research on customers’ dysfunctional behavior (e.g., Fisk et al., ; Huang et al., ), which identified other customers as particularly relevant in service interactions. Vicariously embarrassing incidents, for example, incidents in which a customer cuts in line or argues with a service employee, occur during different types of service transactions and can have substantial consequences on the observing customers’ perception and the evaluation of the service experience.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The results of the empirical analysis reveal that vicarious embarrassment—in which person A feels embarrassed for person B—can occur in situations in which a customer interacts with another customer, as well as in situations in which a customer interacts with a service employee. Overall, by identifying various vicariously embarrassing incidents, the authors were able to support the results of prior research on customers’ dysfunctional behavior (e.g., Fisk et al., ; Huang et al., ), which identified other customers as particularly relevant in service interactions. Vicariously embarrassing incidents, for example, incidents in which a customer cuts in line or argues with a service employee, occur during different types of service transactions and can have substantial consequences on the observing customers’ perception and the evaluation of the service experience.…”
Section: Discussionsupporting
confidence: 66%
“…Furthermore, it can be argued that employees are obligated to react in such situations. As Huang et al (2010) have shown, customers will evaluate a service more negatively when they feel that other customers' misbehavior could have been controlled by the firm. However, if there are only customers present, there is little that the service firm can directly do to resolve the conflict.…”
Section: Parties Involved In the Conflictmentioning
confidence: 99%
“…This type of attribution will inhibit their buying behavior (Huang et al, 2010). As a result, consumers who miss out on a quantity discount are less likely to make a purchase when the promotion scope is perceived to be narrow, regardless of whether MinPR is high or low.…”
Section: Moderator Of Promotion Scopementioning
confidence: 99%
“…However, none of these studies specifically focused on the influence of other customers' service failure observed by the focal customer. In service settings, studies on the role of "other customers" have largely focused on the impact of other customers' misbehavior (Grove and Fisk, 1997;Huang, 2010;Huang et al, 2010) or the presence of other customers themselves as part of the physical service environment such as in crowding situations (Tombs and McColl-Kennedy, 2003) and their effects on the customer service experience. To the best of our knowledge, only one study has attempted to investigate how customers respond to service failures that affect other customers.…”
Section: Introductionmentioning
confidence: 99%